Human Resource Governance in Crisis Situations: Strategies for Effective Management - Abedini, Nikoo; Falsafi Fard, Mona; Bakhshayesh Ardestani, Saba; Alaee, Narges; Askari Masuleh, Saeid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aims to explore the role of human resource governance in managing crisis situations, identifying effective strategies for enhancing organizational resilience and ensuring employee well-being. Methods: Employing a qualitative research design, this study gathered data through semi-structured interviews with 30 participants across multiple industries known for facing significant crises, including healthcare, emergency services, and manufacturing. The interview guide focused on decision-making processes, communication strategies, employee well-being, and crisis preparedness. Data were analyzed using thematic analysis to identify key themes and categories, with theoretical saturation guiding the conclusion of data collection. Findings: The analysis revealed four main themes central to effective HR governance in crisis situations: Decision Making, Communication Strategies, Employee Well-being, and Crisis Preparedness. Under Decision Making, the importance of agile and informed processes was highlighted, emphasizing rapid response strategies, leadership roles, and policy adaptation. Communication Strategies identified the need for effective internal and external communication channels, utilizing technology for broader reach and efficiency. Employee Well-being stressed comprehensive support for mental and physical health, alongside ensuring job security. Lastly, Crisis Preparedness focused on risk assessment, policy development, and staff training to enhance response capabilities. Conclusion: The study concludes that strategic human resource governance plays a pivotal role in navigating crisis situations effectively. The ability of HR practices to adapt quickly and efficiently, coupled with a focus on comprehensive communication, employee support, and preemptive preparedness, is crucial for maintaining operational continuity and safeguarding employee well-being. These findings contribute to the broader understanding of crisis management, offering a framework for organizations seeking to enhance resilience and prepare for future challenges.